Characterisation of nutraceutical compounds from different parts of particular species of Citrus sinensis 'Ovale Calabrese' by UHPLC-UV-ESI-HRMS. Issue 2 (17th January 2019) - Celano, Rita; Campone, Luca; Pagano, Imma; Carabetta, Sonia; Di Sanzo, Rosa; Rastrelli, Luca; Piccinelli, Anna Lisa; Russo, Mariateresa
Abstract: Consumers are aware of diet causing health problems and therefore there is an increased demand for natural ingredients that are expected to be safe and health-promoting. Many of these compounds belong to the class of flavonoids and can be divided into these five groups: flavanones, flavones, flavonols, flavanols, isoflavones and anthocyanidins. Extracts from citrus fruits are usually used as functional ingredients for several products. The aim of this paper was to develop an UHPLC-UV-ESI-HRMS method to define the metabolite profile of different parts of citrus fruit, of a particular cultivar called 'Ovale Calabrese', and in its main by-products. The high resolution mass spectrometry analysis allowed the identification of 27 compounds belonging to the classes of flavonoids and terpenoids. The high contents of phytochemical compounds, reveal the potential use of the 'Ovale Calabrese' as a rich source of nutraceutical compounds. Abstract :